Flash Radiotherapy: Innovative Cancer Treatment - Chow, James C. L.; Ruda, Harry E. (Encyclopedia (Basel, Switzerland), 2023)
Flash radiotherapy (Flash-RT) is an innovative technique used in radiotherapy for cancer treatment because it delivers an extremely high dose of radiation (>40 Gy/s) to the tumour in a very short period of time, typically within a fraction of a second. This ultra-fast delivery of radiation distinguishes Flash-RT from conventional radiotherapy, which typically involves the delivery of radiation over a longer time period, often several minutes. Studies conducted in cell and preclinical models suggested that Flash-RT may spare normal tissues from radiation-related side effects, such as skin toxicity, gastrointestinal complications, and damage to organs-at-risk. This is believed to be due to the unique normal tissue response to the ultra-high dose rate. Nevertheless, while Flash-RT shows promising results in preclinical and early clinical studies, one should note that the technique is still in the early stages of development. This entry provides a comprehensive exploration of the immense potentials of Flash-RT, covering its background, mechanisms, radiation sources, recent experimental findings based on cell and preclinical models, and future prospects. It aims to provide valuable insights into this innovative radiotherapy technology for anyone interested in the subject.